Incorporation of oxidized debranched starch/chitosan nanoparticles for enhanced hydrophobicity of corn starch films. (March 2023) - Liu, Qing; Gao, Lin; Qin, Yang; Ji, Na; Dai, Lei; Xiong, Liu; Sun, Qingjie
Abstract: Starch films have superior advantages owing to the renewability and low cost of starch; however, their strong inherent hydrophilic character greatly limits their practical application. This study aimed to improve the hydrophobicity of corn starch films by adding a new type of covalently formed, oxidized debranched starch/chitosan nanoparticles (SC-NPs). SC-NPs were obtained by a Schiff-base crosslinking reaction between the aldehyde group of dialdehyde debranched starch and the amino group of chitosan. Corn starch films reinforced with SC-NPs were obtained using a casting method. A mass ratio of dialdehyde debranched starch and chitosan of 3–5 yielded mainly spherical nanoparticles ranging from 50 to 150 nm in diameter determined by transmission electron microscopy. The water contact angle (WCA) of the pure starch film was only 19.4°, whereas the WCA values of the films reinforced with 3 % SC-NPs were greater than 70°, indicating that SC-NPs efficiently improved the hydrophobicity of corn starch films. The ultraviolet and visible light barrier property of starch films with 3 % SC-NPs were significantly enhanced in comparison with pure starch film. The water vapor permeability, water solubility, and swelling ratio were markedly lower in films with 3 % SC-NPs than in neat starch films. Graphical Abstract: ga1 Highlights: Oxidized debranched starch/chitosan nanoparticles (SC-NPs) were covalently formed. The size of SC-NPs ranged from 80 to 150 nm. SC-NPs efficiently improved the hydrophobicity of corn starch films. The water contact angle of starch films with 3% SC-NPs was as high as 78.9 ± 1.7°.